The Productivity Convergence Debate: A Theoretical and Methodological Reconsideration - Bruce Elmslie; William Milberg (Levy Economics Institute of Bard College, 1994)
Two fundamental issues have been ignored in the convergence debate which are addressed in this paper. First, there has been little attention paid to the development of a general model able to explain convergence a divergence. Second, in the rush to put data to a convergence hypothesis, researchers have failed to consider certain methodological procedures with respect to the treatment of capital. To remedy this problem we use an input-output approach to measure catch-up. To address the theoretical lacunae we present case studies of Portugal and Japan, two countries which by 1959 had attained the threshold level of development required to join the convergence- club , but which, for various historical (path-dependent) reasons, have diverged rapidly from each other in the period since the late 1950 s.
Keywords: O4; F02; 330